Trends in Moral Understanding in Modern Society Research - Ega Diana; Lidra Agustina Tanjung (International Journal Labs, 2022)
Background: The progress of the current era greatly affects the Islamic community in Indonesia, especially in terms of morals. Nowadays, society is faced with an era that is all modern. Not only in terms of technology, education and the economy are affected, but human morals are also affected by modernization. Purpose: To know what is meant by morals. To find out how the moral phenomenon of society in modern times. To know how to provide a good understanding of morals for the community. Method: This study uses a qualitative approach with a descriptive model to explain the context of each variable. Result: A person is said to be moral if his behavior always reflects kindness without requiring thought. When the deed is firmly ingrained in a person then the morals will become a part of him. Usually, the morals formed through habituation it is not based on the pressure and coercion of others, but arise from within themselves, due to the result of the learning process that it has carried out. Conclusion: Providing a good moral understanding for society is by understanding how Islam teaches how we live our lives and understanding the truth about good and bad morals so that in addition to understanding, society can also practice how the concept of morals is.